INOVASI DAERAH (Refleksi dan Pengaturan Inovasi Daerah di Indonesia) - Made Gde Subha Karma Resen (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
Regional Innovation is an important factor to encourage competitiveness and prosperity in the region. Innovation is a collaborative process to improve effectiveness and efficiency in the Region. Innovation cannot run sporadically and partially, particularly at the level of regulation and governance. Reflection on experience shows, government apprehensive to innovate in the Region. Criminalization of policy, euphoria of corruption eradication causing poor innovation in the Region, so it should be given the rule that provides the flexibility to innovate without diminishing accountability or in formulating innovation policy, should be based on the principles in the running of innovation. Through the juridical analysis of substance of the Law 23/2014, have been set related to regional innovation. There is the possibility of expanding the activities of government, with narrowing of the risk of criminal prosecution.